Incorrect inhaler techniques in Western India: still a common problem - Sodhi, Mandeep Kaur (International Journal of Research in Medical Sciences, 2017)
Background: To assess and evaluate the incorrect use of inhalers in patients with asthma and chronic obstructive pulmonary disease (COPD) in the outpatient department of pulmonary medicine at RUHS college of medical sciences Jaipur, Rajasthan, India. Methods: Patients visiting the outpatient department of respiratory medicine were asked to demonstrate the inhaler technique and were assessed by the physician. Results: The study included 200 patients with Asthma or COPD. Among patients with COPD, 80 (63.4%) were males and 46 (36.5%) were females. In the asthma group, there were 50 (67.5%) females and 24 (32.4%) males. Patients with COPD were in the age group between 46-82 years with a mean age of 64 years while patients with asthma were in the age group between 18-70 years with a mean age of 44 years. Only 28 (14%) patients could perform all steps correctly in use of inhaler devices. 172 patients (86%) were unable to use inhalers properly. Most common error for metered dose inhalers (MDIs) was in step 7 that is (i.e.) not holding breath for 10 seconds which was seen in 46 patients (51.7%). The most common error seen for dry powder inhalers (DPIs) was in step 5 i.e. exhalation to residual volume before inhalation seen in 50 patients (47.1%). Conclusions: This study revealed that majority of patients use the inhaler devices incorrectly. Proper education regarding inhaler use is crucial for effective treatment with use of these inhaler devices.